Upaya Pencegahan Tindakan Korupsi terhadap Pemangku Kepentingan Melalui Pelaksanaan Hukum Negara - Gabriel Varel Contessa Dupa (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This abstract discusses the importance of preventing corruption through effective implementation of the law, especially in relation to stakeholders. Corruption is a serious threat to public trust and the stability of government and private institutions. Strict and fair application of the law is very necessary to create a transparent and accountable environment. By implementing clear rules and heavy sanctions, acts of corruption can be minimized. Active participation of stakeholders, including government, civil society and the private sector, is also very necessary in monitoring and supporting efforts to prevent corruption. This will create good governance and strengthen public trust in institutions.